Estudo das propriedades viscoelásticas de células - Costa, Damião Ferreira da Silva (2019)
In this work a quantitative study was performed on the viscoelastic properties of cells through computational simulations with direct application of the Finite Element Method (FEM). The simulated experiment consists of a relaxation test, in which a constant indentation was applied under a viscoelastic cell through a spherical bead of Atomic Force Microscopy (AFM). Different viscoelastic cells were constructed in relation to the geometry and the indentations were performed at different points on the cell surface. Using the built models, we vary the cytoplasmic stiffness in order to obtain a kind of mechanical signature for each value corresponding to the established G shear, from the analysis of the force curves. Our results show that the curves obtained may vary according to the indented location, geometry used, indentation depth, cell type and state of health. In addition, the viscoelastic response depends on the experiment execution time when compared to the material specific time.